-3=1+n/9

Simple and best practice solution for -3=1+n/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=1+n/9 equation:



-3=1+n/9
We move all terms to the left:
-3-(1+n/9)=0
We add all the numbers together, and all the variables
-(n/9+1)-3=0
We get rid of parentheses
-n/9-1-3=0
We multiply all the terms by the denominator
-n-1*9-3*9=0
We add all the numbers together, and all the variables
-1n-36=0
We move all terms containing n to the left, all other terms to the right
-n=36
n=36/-1
n=-36

See similar equations:

| -9f=21 | | 0.4x+4=0.2x+8 | | (7x+3)+90+(3x+7)=180 | | -5c-6=24 | | 3(2x+6)-9=2x-(5x+9) | | 1/2x+9=6 | | -13x-13=-273 | | 8+a=-10 | | w/(-3)+14=5 | | 104-3x=89 | | x^2-4x+15=2x+22 | | 4d-5=15 | | x/5+10=-6 | | 2w+5=60 | | -36=8-4c | | 39-2b=3(b-1)+2 | | 3x2+40x-675=0 | | x^{2}=121 | | 0=x^2+1x-1 | | 3r-9=r | | -48=7+5w | | 10x-3=5x-18 | | 16j+10j+(-14j)=12 | | -n+2(n+4)=-1-8n | | 6=5h=6 | | 4(x-3)=2(x-10) | | -13x-13=273 | | -10=r/2​ | | 2h+35=106 | | -6r-32=-r-5(r+7) | | 6x+4x-13=27 | | 8x+4x+2x+2+10=180 |

Equations solver categories